2016
DOI: 10.4103/2152-7806.196933
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal right-optic nerve Rosai-Dorfman disease: A rare localization case report

Abstract: Background:Rosai–Dorfman is a rare disease that usually occurs in young adults. It is characterized with massive painless cervical lymphadenopathy and histiocyte proliferation. Isolated intracranial involvement is extremely rare. Our aim is to present a new rare case of extranodal Rosai–Dorfman disease that involved the right optic nerve in a 4-year-old boy.Case Description:A 4-year-old boy with right-sided convergent strabismus and amblyopia lasting for 1 year was treated at the Department of pediatric ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[1314] The differential diagnosis also sometimes includes lymphoma, malignant histiocytosis, and monocytic leukemia. [67] The differential diagnoses may also include granulomatous inflammatory diseases, inflammatory idiopathic pseudotumors. [15] In the presence of numerous plasma cells, as in our case, the pathological differential diagnosis may also include IgG4-related disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1314] The differential diagnosis also sometimes includes lymphoma, malignant histiocytosis, and monocytic leukemia. [67] The differential diagnoses may also include granulomatous inflammatory diseases, inflammatory idiopathic pseudotumors. [15] In the presence of numerous plasma cells, as in our case, the pathological differential diagnosis may also include IgG4-related disease.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Orbit and ocular glove involvement have been reported, usually as a retro-orbital mass and proptosis. [67] We report a case of extranodal RDD in a 53-year-old man who presented with right orbital mass.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment of RDD is indicated for extranodal forms of disease that are affecting vital structures; however, remissions with surgery alone have been reported in CNS-only disease [14,30]. Total resection of the intracranial lesion may be curative [3,20]. The majority of patients remain disease-free for prolonged periods of time [14].…”
Section: Treatment Of Extranodal Intracranial Rddmentioning
confidence: 99%
“…There are only few cases of extranodal intracranial disease described in pediatric population so far. Recently intracranial RDD in pediatric patient was also successfully treated in our country [20]. We aimed to provide updated comprehensive review of reported extranodal intracranial RDD in children.…”
Section: Introductionmentioning
confidence: 99%